Primary School Extracurricular Music Activities in Covasna and Harghita Counties - Bartalis, Izabella (Central European Journal of Educational Research, 2021)
Arts education, including music teaching (Dohány, 2010) in elementary schools is getting less and less importance in our present day education system, accordingly we find quite relevant to investigate the situation of music teaching in Romania among the Hungarian minority educationís elementary classes. This present study would like to map the extracurricular fields of music teaching in Covasna and Harghita counties in Hungarian classes through a questionnaire research made among teachers. Our objective is to investigate extracurricular musical education in elementary classes, where we would like to find out what kind of musical activities exist in this area and how intensively do pupils take part in these activities. The self-made questionnaire was sent out online in Covasna and Harghita counties, based on the teachers ‘database at the end of January in 2020. 78 elementary school teachers took part in this research. All the collected data was processed with the help of a statistical data analysing software, examining the descriptive statistical indicators. The analysis shows that few elementary class students take part in extracurricular activities. Romanian music pedagogy research do not extend to Hungarian minority classes, thus we see it important to investigate the extracurricular activities in counties where Hungarian minorities live.